Extracellular concentrations of catecholamines and amino acids in the dorsomedial hypothalamus of kindled rats - A Microdialysis Study - ONAT, FİLİZ; YANANLI, HASAN RACİ; GÜLHAN, REZZAN (KARGER, 2003)
Epilepsy affects homeostasis and autonomic nervous system functions. It has been thought that the dysfunction in the autonomic neural mechanisms could be a cause of sudden unexpected death in patients with epilepsy. The kindling model of epilepsy is considered to be an animal model for complex partial seizures with secondary generalization. The objectives of this study were to investigate the extracellular gamma-aminobutyric acid (GABA), glutamate, noradrenaline and dopamine levels in the dorsomedial nucleus of the hypothalamus in nonepileptic and kindled epileptic rats and to explain some of the cardiovascular changes in the kindling model of epilepsy. Stimulation electrodes were stereotaxically implanted into the basolateral amygdala and electrical stimulation was applied 3 times a day at a constant current. The rats were then kindled to full stage 5 seizures. Microdialysis experiments were performed to demonstrate the neurotransmitter levels in the dorsomedial nucleus of the hypothalamus 3-5 days after being kindled. Decreases in noradrenaline and dopamine levels in the dorsomedial nucleus were detected in the conscious kindled animals. This finding is in agreement with prior findings that the noradrenergic system has a negative role in the process of kindling. The basal level of glutamic acid and GABA remained unchanged in the kindled group when compared to non-epileptic animals, and similarly, neither blood pressure nor heart rate responses to bicuculline or N-methyl-D-aspartate were affected by the acute kindled state. These findings suggest that the autonomic changes in kindling require further studies. Copyright (C) 2003 S. Karger AG, Basel.
Keywords: kindling; dorsomedial nucleus of hypothalamus; noradrenaline; dopamine; glutamate; gamma-aminobutyric acid (GABA); SUDEP; AUTONOMIC DYSFUNCTION; NORADRENERGIC ABNORMALITIES; CARDIOVASCULAR-RESPONSES; CARDIAC-ARRHYTHMIAS; UNEXPLAINED DEATH; HEART-RATE; AMYGDALA; EPILEPSY; SEIZURE; NORADRENALINE